Generalized event knowledge activation during online sentence comprehension - Metusalem, Ross (2012)
Recent research has demonstrated that knowledge of real-world eventsplays an important role inguiding online language comprehension. The present study addresses the scope of event knowledge activation during the course of comprehension, specifically investigating whether activation is limited to those knowledge elements that align with the local linguistic context.The present study addresses this issue by analyzing event-related brain potentials (ERPs) recorded as participants read brief scenariosdescribing typical real-world events. Experiment 1 demonstratesthat a contextually anomalous word elicits a reduced N400 if it is generally related to the described event, even when controlling for the degree of association of this word with individual words in the preceding context and with the expected continuation. Experiment 2 shows that this effect disappears when the discourse context is removed.These findings demonstrate that during the course of incremental comprehension, comprehenders activate general knowledge about the described event, even at points at which this knowledge would constitute an anomalous continuation of the linguistic stream. Generalized event knowledge activationcontributes to mental representations of described events, is immediately available to influence language processing, and likely drives linguistic expectancy generation.